AllergoOncology: Opposite outcomes of immune tolerance in allergy and cancer. Issue 2 (5th October 2017) - Jensen‐Jarolim, E.; Bax, H. J.; Bianchini, R.; Crescioli, S.; Daniels‐Wells, T. R.; Dombrowicz, D.; Fiebiger, E.; Gould, H. J.; Irshad, S.; Janda, J.; Josephs, D. H.; Levi‐Schaffer, F.; et al.
Abstract: While desired for the cure of allergy, regulatory immune cell subsets and nonclassical Th2‐biased inflammatory mediators in the tumour microenvironment can contribute to immune suppression and escape of tumours from immunological detection and clearance. A key aim in the cancer field is therefore to design interventions that can break immunological tolerance and halt cancer progression, whereas on the contrary allergen immunotherapy exactly aims to induce tolerance. In this position paper, we review insights on immune tolerance derived from allergy and from cancer inflammation, focusing on what is known about the roles of key immune cells and mediators. We propose that research in the field of AllergoOncology that aims to delineate these immunological mechanisms with juxtaposed clinical consequences in allergy and cancer may point to novel avenues for therapeutic interventions that stand to benefit both disciplines. Abstract :